Fourier multipliers on anisotropic mixed-norm spaces of distributions - Cleanthous, Galatia; Georgiadis, Athanasios G.; Nielsen, Morten (MATHEMATICA SCANDINAVICA, 2019)
A new general Hörmander type condition involving anisotropies and mixed norms is introduced, and boundedness results for Fourier multipliers on anisotropic Besov and Triebel-Lizorkin spaces of distributions with mixed Lebesgue norms are obtained. As an application, the continuity of such operators is established on mixed Sobolev and Lebesgue spaces too. Some lifting properties and equivalent norms are obtained as well.